2014
DOI: 10.1111/bcpt.12207
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Cytotoxicity in Cancer

Abstract: Selenium is an essential trace element with growth-modulating properties. Decades of research clearly demonstrate that selenium compounds inhibit the growth of malignant cells in diverse experimental model systems. However, the growth-modulating and cytotoxic mechanisms are diverse and far from clear. Lately, a remarkable tumour selective cytotoxicity of selenium compounds has been shown, indicating the potential of selenium in the treatment of cancer. Of particular interest are the redoxactive selenium compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 65 publications
1
77
0
5
Order By: Relevance
“…The vital elements such as copper, Zn, and Se are connected together in cytosolic defense against reactive oxygen and nitrogen species (18). Human and laboratory studies have been conducted on the role of these 2 elements in preventing carcinogenesis process and tumor cell growth (19)(20)(21)(22). On the other hand, epidemiological studies have shown that differences in dietary habits or diet (23,24) and air pollution (25) can effect on risk of BC, in line with genetics (26).…”
Section: Discussionmentioning
confidence: 99%
“…The vital elements such as copper, Zn, and Se are connected together in cytosolic defense against reactive oxygen and nitrogen species (18). Human and laboratory studies have been conducted on the role of these 2 elements in preventing carcinogenesis process and tumor cell growth (19)(20)(21)(22). On the other hand, epidemiological studies have shown that differences in dietary habits or diet (23,24) and air pollution (25) can effect on risk of BC, in line with genetics (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most probes used for the determination of superoxide ions are not specific and can react with other species (11). For example, nitroblue tetrazolium reacts with selenolate anions in the absence of dioxygen 3 and therefore cannot be used to monitor superoxide production. To indirectly demonstrate the production of superoxide during selenol oxidation, we studied the effect of SOD on the rate of the auto-oxidation reaction.…”
Section: H 2 Se Production Is Not Involved In Semetmentioning
confidence: 99%
“…At supranutritional levels, there are indications that selenium has anticarcinogenic and disease preventing properties. However, at higher doses selenium compounds are toxic, and the gap between toxic and prophylactic or therapeutic doses is narrow (2,3). Numerous studies were performed to evaluate the toxic effects of different forms of selenium, either organic, such as selenomethionine (SeMet), or inorganic, such as selenite.…”
mentioning
confidence: 99%
“…Moreover, in approximately all organic and inorganic sulfur compounds, selenium can substitute sulfur [21].…”
Section: Resultsmentioning
confidence: 99%